Hubungan antara persepsi dukungan sosial dan resiliensi pada orang tua anak berkebutuhan khusus: The Relationship Between Social Support Perception and Resilience Among Parent With Special Needs Kids - Ali, Mauna; Gazadinda, Rahmadianty; Rahma, Novaria (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2020)
This study aims to determine the positive relationship between perceived social support and resilience in parents of childrenwith special needs. Resilience can be used by parents as a source of strength in the face of adversity. The instruments used in this study is were the Multidimensional Scale of Perceived Social Support (MSPSS) developed by Zimet (1988) to measure the perceived social support and Connor Davidson Resilience Scale (CD-RISC) developed by Connor and Davidson (2003) for resilience variables. The sample in this study amounted to 164 parents who have children with special needs. This research uses purposive sampling technique. Method of data analysis in testing hypotheses using correlation techniques. The analysis results showed that the significance (p) of 0,000 (p<0,05). Based on these results, it can be conclude that the hypothesis of this study has been accepted, which stated that there is was a significant relationship between the perceived social support and resilience in parents of children with special needs.